Treatment of Oral Pyogenic Granuloma by 810 nm Diode Laser - Mahmood, Ali S. (Iraqi Journal of Laser, 2008)
Pyogenic granuloma is one of the inflammatory hyperplasia seen in the oral cavity. The present study included 10 patients with pyogenic granuloma, involving 4 males and 6 females with 1:1.5 male to female ratio. Patient ages ranged from 5 to 85 years (mean, 30 years) and half of the lesions had pedunculated base, with surface ulceration in 10% of cases. Treatment consisted of resection, using 810 nm diode lasers. Eight patients were anesthetized during the surgical operation by local infiltration of anesthesia. Only three patients reported mild post-operative pain within the first 24 hours of the healing period. During the surgical operation there was no significant bleeding so clear surgical field. There was no bleeding postoperatively. There was mild edema appear in first 2 days after the surgery, and then it subsided gradually. There was no infection in all the patients treated. One day following the operation the intra oral examination showed dark-brown necrotic tissue, friable with red inflamed line around the edges. After five days, the observation revealed that the sloughs tissue was completely changed to white color and was easily removed by gauze. Wound healing was excellent after only one week. All the samples were diagnosed histopathologically as pyogenic granuloma.